The Sexual Advantage of Looking, Smelling, and Tasting Good: The Metabolic Network that Produces Signals for Pollinators. (April 2017) - Borghi, Monica; Fernie, Alisdair R.; Schiestl, Florian P.; Bouwmeester, Harro J.
Abstract : A striking feature of the angiosperms that use animals as pollen carriers to sexually reproduce is the great diversity of their flowers with regard to morphology and traits such as color, odor, and nectar. These traits are underpinned by the synthesis of secondary metabolites such as pigments and volatiles, as well as carbohydrates and amino acids, which are used by plants to lure and reward animal pollinators. We review here the knowledge of the metabolic network that supports the biosynthesis of these compounds and the behavioral responses that these molecules elicit in the animal pollinators. Such knowledge provides us with a deeper insight into the ecology and evolution of plant-pollinator interactions, and should help us to better manage these ecologically essential interactions in agricultural ecosystems. Trends: Novel routes for the biosynthesis of floral volatiles in unusual subcellular compartments are being identified and new theories on the emission of scent are proposed. Key genes in betalain biosynthesis have been identified and new theories on the evolutionary origin of the pathway have been suggested. Master regulators that coordinately control the production of pigments and scent in flowers are emerging. Loci have been identified that contribute to reproductive isolation by pollination preferences for visual and olfactory cues and ultimately lead to speciation.